2010
DOI: 10.1007/s00296-010-1523-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with temporary work disability in patients with fibromyalgia

Abstract: Temporary work disability (TWD) is more common in patients with fibromyalgia (FM) than among the rest of the workers. To describe the differences between patients who take sick leave (TWD group) and those who continue to work regularly (control group). To determine what factors are associated with TWD. Multicentre, cross-sectional study with a cohort of patients with FM seen in rheumatology clinics throughout Spain. The following information was recorded: demographic data, clinical manifestations, comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
0
16
1
5
Order By: Relevance
“…The severity of the disease has also been shown to influence the rate of charges incurred, that is, the greater the disease severity, the greater the costs. [25][26][27] In 2013, Knight et al reported that the direct medical costs of fibromyalgia patients in the United States are significantly greater than the costs of patients in Germany and France (US $7,087, US$2,417, and US$481, respectively). 28 These costs were mainly attributable to prescriptions medications, patient out-of-pocket costs, and physician office visits.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the disease has also been shown to influence the rate of charges incurred, that is, the greater the disease severity, the greater the costs. [25][26][27] In 2013, Knight et al reported that the direct medical costs of fibromyalgia patients in the United States are significantly greater than the costs of patients in Germany and France (US $7,087, US$2,417, and US$481, respectively). 28 These costs were mainly attributable to prescriptions medications, patient out-of-pocket costs, and physician office visits.…”
Section: Discussionmentioning
confidence: 99%
“…Son conscientes de que sobre ellas recae 23 , a lo que contribuye tener acceso a directivos sensibilizados sobre la gravedad y consecuencias de la enfermedad, que no les sometan a cuestionamientos 21,24 .…”
Section: Dificultades Para Cumplir Las Exigencias Laboralesunclassified
“…Para la interpretación de este resultado, también cabe tener en cuenta que, en España, la única alternativa remunerada al empleo contemplada por la Seguridad Social es la de recibir una prestación por incapacidad. Sin embargo, es un proceso arduo y lento que exige grandes esfuerzos económicos y psicológicos, y que no siempre genera los resultados esperados 21,25 . Continuar trabajando requiere cambios no solo en las personas afectadas sino también en las propias condiciones de trabajo.…”
Section: Las Estrategias Adoptadas Para Continuar Trabajandounclassified
See 1 more Smart Citation
“…Entretanto, também menciona que sejam feitas mudanças no ambiente do trabalho, readaptação profi ssional e redução da carga horária para funcionários com quadro sugestivo da síndrome de dor crônica. Já Reisine et al 24 e Rivera et al 25 concluem que os pacientes portadores de fi bromialgia que continuam trabalhando apresentam melhor resposta clínica ao tratamento quando comparado àqueles que não trabalham. Isso sugere que o trabalho é fator positivo no prognóstico e atua de forma benéfi ca na diminuição da intensidade dos sintomas provocados pela fi bromialgia 26 .…”
Section: Segundo Dados Do Ministério Da Previdênciaunclassified